Effectiveness of school-based smoking prevention education program (SPEP) among nonsmoking adolescents: A Quasi-experimental study - Nurumal, Mohd Said; Zain, Siti Hajar Mohd; Nik Mohamed, Mohamad Haniki; Shorey, Shefaly (SAGE Publishing, 2019)
Preventing smoking among adolescents is critical. This study evaluated the effectiveness of the Smoking Prevention Education Program among nonsmoking adolescents. A quasi-experimental study design was used. Data were collected from Year 5 students (n = 140) from four government primary schools in the Kuantan and Pahang districts of Malaysia. The participating schools were randomly assigned into the intervention and control groups. Questionnaires and exhaled carbon monoxide (CO) levels were used to collect data at the baseline and at 3 months postintervention. At 3 months postintervention, the percentage of nonsmokers remained 100% in the intervention group, while 2.9% of the participants in the control group reported to have smoked in past 7 days. Comparatively, the mean scores of attitudes, subjective norms, and nonsmoking intentions of the intervention group improved significantly. The intervention was effective in preventing smoking initiations among Malaysian adolescents; however, further evaluation of this intervention is needed among varied populations.